Learning Loss Literasi dan Numerasi Pascapandemi: Studi Kasus Di SMKN 1 Amabi Oefeto Timur, Kabupaten Kupang, Nusa Tenggara Timur - Irsanki Gabrial Poa; Erni Murniarti; Lisa G Kailola (LPPM Institut Pendidikan Nusantara Global, 2026)
Post-pandemic declines in students' literacy and numeracy remain a serious concern in 3T areas of East Nusa Tenggara (NTT). This study aimed to identify the factors associated with literacy and numeracy learning loss in secondary schools in 3T areas of NTT and to examine their relevance to SMKN 1 Amabi Oefeto Timur, Kupang Regency. The study used a Systematic Literature Review (SLR) design guided by the PRISMA protocol. Literature searches were conducted through Google Scholar, Portal Garuda, SINTA, and DOAJ for publications issued between 2015 and 2025. After screening 237 initial records, 28 articles met the inclusion criteria and were analyzed thematically. The synthesis shows that learning loss is related to six interconnected factors: infrastructure limitations, geographical barriers, socio-economic conditions, pedagogical constraints, sociocultural factors, and pandemic-related disruptions. Infrastructure and socio-economic factors appeared most consistently in the reviewed studies, while the pandemic functioned as an accelerator of pre-existing inequalities. The relationship among factors forms both hierarchical and cumulative patterns. Geographical barriers affect infrastructure and learning access, while socio-economic and sociocultural conditions mutually reinforce students' limited learning support. In the context of SMKN 1 Amabi Oefeto Timur, the findings suggest the need for diagnostic assessment, remedial instruction, stronger family engagement, and locally relevant literacy-numeracy support. The study is limited by its reliance on secondary data and the absence of primary field data from the school. These findings may serve as evidence for designing recovery programs that are more responsive to the conditions of 3T schools in NTT.